Structural characterization of CAS SH3 domain selectivity and regulation reveals new CAS interaction partners - Jakub Gemperle; Rozálie Hexnerová; Martin Lepšík; Petr Tesina; Michal Dibus; Marian Novotný; Jan Brábek; Václav Veverka; Daniel Rosel (Scientific Reports, 2017)
Abstract CAS is a docking protein downstream of the proto-oncogene Src with a role in invasion and metastasis of cancer cells. The CAS SH3 domain is indispensable for CAS-mediated signaling, but structural aspects of CAS SH3 ligand binding and regulation are not well understood. Here, we identified the consensus CAS SH3 binding motif and structurally characterized the CAS SH3 domain in complex with ligand. We revealed the requirement for an uncommon centrally localized lysine residue at position +2 of CAS SH3 ligands and two rather dissimilar optional anchoring residues, leucine and arginine, at position +5. We further expanded the knowledge of CAS SH3 ligand binding regulation by manipulating tyrosine 12 phosphorylation and confirmed the negative role of this phosphorylation on CAS SH3 ligand binding. Finally, by exploiting the newly identified binding requirements of the CAS SH3 domain, we predicted and experimentally verified two novel CAS SH3 binding partners, DOK7 and GLIS2.